2003
DOI: 10.1159/000068745
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular Schwannoma, Tinnitus and Cellular Telephones

Abstract: Cases with tinnitus after using analogue cellular telephones are presented. An increased odds ratio of 3.45, 95% confidence interval (CI) 1.77–6.76, was found for vestibular schwannoma (VS) associated with the use of analogue cell phones. During the time period 1960–1998, the age-standardized incidence of VS in Sweden significantly increased yearly by +2.53% (CI 1.71–3.35). A significant increase in the incidence of VS was only found for the latter of the two time periods 1960–1979 and 1980–1998. For all other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 13 publications
4
36
0
1
Order By: Relevance
“…In two previous studies, we have found an increased risk for brain tumors associated with cellular telephone use [1][2][3][4][5][6] . The risk was highest on the side of the brain Unconditional logistic regression analysis adjusted for age, sex, SEI and year of diagnosis was used.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…In two previous studies, we have found an increased risk for brain tumors associated with cellular telephone use [1][2][3][4][5][6] . The risk was highest on the side of the brain Unconditional logistic regression analysis adjusted for age, sex, SEI and year of diagnosis was used.…”
Section: Discussionmentioning
confidence: 82%
“…This is the third case-control study showing a link between signifi cantly increased risk for acoustic neuroma and cellular telephone use [5,6,19] . Regarding meningioma, a somewhat increased risk was found, although the association was not as clear as for acoustic neuroma.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Another paper by Hardell et al 28 13 , which also compared 159 acoustic neuroma, 611 meningioma and 1617 combined tumour cases with 1 control per case (1997)(1998)(1999)(2000); reanalyses of the same data were also published elsewhere 15,[30][31][32][33] . Overall, it was reported 13 that MP use was associated with increased risk of acoustic neuroma for analogue (38 cases; 3.5[1.8-6.8]) but not digital or cordless MPs, with similar analogue risks for > 5 year and > 10 year groups.…”
Section: Population-based Case-control Designsmentioning
confidence: 99%
“…Over the evolution of these studies there has been continuing refinement in the exposure assessment methods, although the techniques for exposure assessment are far from ideal [Ahlbom et al, 2004]. Self-report of mobile phone use has been the primary method used so far in the retrospective casecontrol studies [Hardell et al, 1999[Hardell et al, , 2001[Hardell et al, , 2003aMuscat et al, 2000Muscat et al, , 2002Christensen et al, 2001Christensen et al, , 2004Inskip et al, 2001;Johansen et al, 2001;Auvinen et al, 2002;Warren et al, 2003;Cardis et al, 2007]. The accuracy of self-reported exposure information and the potential biases introduced by recall or reporting have always been a concern for the design of case-control studies, in general Berg et al, 2005;Vrijheid et al, 2006].…”
Section: Introductionmentioning
confidence: 99%